2018
DOI: 10.1038/s41598-017-18283-0
|View full text |Cite
|
Sign up to set email alerts
|

Flt3 ligand expands bona fide innate lymphoid cell precursors in vivo

Abstract: A common helper-like innate lymphoid precursor (CHILP) restricted to the innate lymphoid cells (ILC) lineage has been recently characterized. While specific requirements of transcription factors for CHILPs development has been partially described, their ability to sense cytokines and react to peripheral inflammation remains unaddressed. Here, we found that systemic increase in Flt3L levels correlated with the expansion of Lineage (Lin)negα4β7+ precursors in the adult murine bone marrow. Expanded Linnegα4β7+ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…The plasma Flt3L increase observed in acute, uncomplicated falciparum or knowlesi malaria, are consistent with previous studies that found plasma Flt3L levels to be increased in clinical disease [19,20]. In children, Flt3L levels are significantly higher in severe malaria patients compared to uncomplicated malaria patients [19], however, Flt3L concentrations reported in uncomplicated malaria in children are lower than those recorded in adults in this study and by others [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The plasma Flt3L increase observed in acute, uncomplicated falciparum or knowlesi malaria, are consistent with previous studies that found plasma Flt3L levels to be increased in clinical disease [19,20]. In children, Flt3L levels are significantly higher in severe malaria patients compared to uncomplicated malaria patients [19], however, Flt3L concentrations reported in uncomplicated malaria in children are lower than those recorded in adults in this study and by others [20].…”
Section: Discussionsupporting
confidence: 92%
“…In children with severe P. falciparum malaria, Plasmodium -induced Flt3L is reported to selectively stimulate the expansion of blood CD141 + DCs, but not other DC subsets [ 19 ]. Increased Flt3L is observed in adults with uncomplicated P. falciparum malaria [ 20 ], yet associations with DCs have not been investigated in adults. Here, plasma Flt3L and circulating DC numbers were quantified in adults experimentally infected with P. falciparum, and adults with clinical P. falciparum or P. knowlesi malaria to better understand the impact of a Plasmodium infection on circulating DC numbers and their association with plasma Flt3L levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cell isolation from the colonic tissue was performed as previously described 56 with modifications. Briefly, tissues were open longitudinally, cut into 1-cm pieces, and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Cell samples collected from different immune compartments were frozen in 90% heat-inactivated FBS and 10% DMSO (Sigma-Aldrich). Intestinal lamina propria cells were isolated from duodenum, ileum, or colon tissue of rhesus macaques, as previously described for murine tissue (Parigi et al, 2018). Briefly, 5-cm-long intestinal samples were placed in ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%